Pengembangan Elektronik Lembar Kerja Peserta Didik Berbasis Problem Based Learning Pada Materi Perubahan Materi - Widiana Uluk Naikofi; Eny Enawaty; Rody Putra Sartika; Rachamat Sahputra; Rini Muharini (Cetta: Jurnal Ilmu Pendidikan, 2022)
The aim of this study is to determine the worthiness of electronically based learning problems on material changes. Research methods use development this research are the stages of analysis, design and development. The subject in this study is an e-lon-based PBL on matter changes in matter. Data collection techniques are done using technical measurements. Expert validation sheets are used as data collection tools. The feasibility of the product covers three aspects: material, media, language and is done by three scholars for each aspect. Based on the results of research conducted on the feasibility of this product, it was obtained as much as validating 94,25%. based on the validation of spherical material experts based on media validation 97,024% and 92,709% based on language  validation. Data processing shows that the e-lon-based based learning problems is categorized as highly feasible from all three aspects. This result suggests that the e-lto this can be explained as a learning mediumresearch methods through an addie model. The stages in addie models applied to.